Effect of temperature variation on the cytotoxicity of cast dental alloys and commercially pure titanium - Adriana Cláudia Lapria Faria; Renata Cristina Silveira Rodrigues; Rossana Pereira de Almeida Antunes; Maria da Gloria Chiarello de Mattos; Adalberto Luiz Rosa; Ricardo Faria Ribeiro (University of São Paulo, 2009)
Cell culture system has been used to evaluate alloy cytotoxicity under different environments, testing the extracts, but the effect of temperature variation on the cytotoxicity of dental alloys has not been analyzed. OBJECTIVE: The aim of the present study was to investigate if temperature variation could affect dental alloy cytotoxicity, testing alloy extracts in an epithelial cell culture system. MATERIAL AND METHODS: Discs of Ni-Cr, Co-Cr-Mo, Ni-Cr-Ti, Ti-6Al-4V and commercially pure titanium (cp Ti) were cast by arc melting, under argon atmosphere, injected by vacuum-pressure. Discs were immersed in artificial saliva and subjected to different temperatures: 37ºC and thermocycling (37ºC/5ºC/37ºC/55ºC/37ºC). After thermocycling, extracts were put in a subconfluent culture during 6 h, and the number of cells and their viability were used to evaluate cytotoxicity in these temperatures. For each alloy, data from temperature conditions were compared by Student's t-test (α=0.05). RESULTS: The cytotoxicity tests with alloy/metal extracts showed that Ni-Cr, Co-Cr-Mo, Ti-6Al-4V and cp Ti extracts (p>0.05) did not affect cell number or cell viability, while Ni-Cr-Ti (p<0.05) extract decreased cell number and viability when the alloy was subjected to thermocycling. CONCLUSION: Within the limitations of the present study, the Ni-Cr-Ti alloy had cell number and viability decreased when subjected to temperature variation, while the other alloys/metal extracts did not show these results.